A "GAP" in Activation: A Better Way to Manage Geriatric and Anticoagulated Patients with Head Trauma. Issue 7 (July 2022) - Lee, Janet S.; Khan, Abid D.; Brockman, Valerie; Schroeppel, Thomas J.
Background: Older age and anticoagulant use have been associated with worse outcomes in trauma. At the study institution, elderly and anticoagulated patients with suspected traumatic brain injury (TBI) were previously triaged as a second tier trauma team activation (TTA) with a high rate of over-triage. A novel "GAP" (Geriatric or Anticoagulated Pathway) alert was created to streamline care delivery to these patients. The purpose of the study is to assess the efficacy and outcomes of the GAP alert. Methods: A retrospective review was conducted on adult patients presenting to a level-1 trauma center from 1/2018-12/2020. The GAP alert was implemented in 2/2018. The GAP alert group was compared to the second tier TTA group. Results: 1743 patients were identified. 504 (29%) received a GAP alert. GAP alert patients were older (79 years vs 47 years, P < .0001), had a lower injury severity score (ISS) (8.6 vs 9.9, P = . 006), and had a higher rate of pre-injury anticoagulant use (28.4% vs 2.5%, P < .0001). The in-hospital mortality was higher in the GAP group (2.4% vs .7%, P = . 004). On multivariable logistic regression, GAP alert was not identified as a predictor of mortality. Age, ISS, and pre-injury anticoagulant use predicted mortality. During the study period, the number of GAP alerts increased ( B = .15, P = . 003) and the number of second tier TTAs decreased ( B = −.33, P < .0001). Conclusion: Implementation of the GAP alert led to a decrease in trauma resource utilization while providing timely diagnosis and treatment of geriatric patients or those on anticoagulation medication with suspected TBI.